New mechanism for Notch signaling to endothelium at a distance by Delta-like 4 incorporation into exosomes - Sheldon, Helen; Heikamp, Emily; Turley, Helen; Dragovic, Rebecca; Thomas, Peter; Oon, Chern Ein; Leek, Russell; Edelmann, Mariola; Kessler, Benedikt; Sainson, Richard C A; Sargent, Ian; Li, Ji-Liang; et al. (Blood, 2010)
Notch signaling is an evolutionary conserved pathway that is mediated by cell-cell contact. It is involved in a variety of developmental processes and has an essential role in vascular development and angiogenesis. Delta-like 4 (Dll4) is a Notch ligand that is up-regulated during angiogenesis. It is expressed in endothelial cells and regulates the differentiation between tip cells and stalk cells of neovasculature. Here, we present evidence that Dll4 is incorporated into endothelial exosomes. It can also be incorporated into the exosomes of tumor cells that overexpress Dll4. These exosomes can transfer the Dll4 protein to other endothelial cells and incorporate it into their cell membrane, which results in an inhibition of Notch signaling and a loss of Notch receptor. Transfer of Dll4 was also shown in vivo from tumor cells to host endothelium. Addition of Dll4 exosomes confers a tip cell phenotype on the endothelial cell, which results in a high Dll4/Notch-receptor ratio, low Notch signaling, and filopodia formation. This was further evidenced by increased branching in a tube-formation assay and in vivo. This reversal in phenotype appears to enhance vessel formation and is a new form of signaling for Notch ligands that expands their signaling potential beyond cell-cell contact.